2013
DOI: 10.1053/j.sempedsurg.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Fetal surgery for spina bifida: Past, present, future

Abstract: Open spina bifida or myelomeningocele (MMC) is a common birth defect that is associated with significant lifelong morbidity. Little progress has been made in the postnatal surgical management of the child with spina bifida. Postnatal surgery is aimed at covering the exposed spinal cord, preventing infection, and treating hydrocephalus with a ventricular shunt. Experimental and clinical evidence suggest that the primary cause of the neurologic defects associated with MMC is not simply incomplete neurulation, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(49 citation statements)
references
References 67 publications
1
46
0
2
Order By: Relevance
“…The MOMS trial demonstrated conclusively that fetal surgery improves the 12- and 30-month outcomes of MMC patients, with a reduction in hindbrain herniation and the need for shunting and significant improvement in functional neurological outcomes, including the ability to walk without orthotics, setting a new standard for the treatment of eligible MMC fetuses. However, open fetal surgery for MMC is not a cure, with most patients demonstrating some degree of residual neurological deficit and some fetuses demonstrating no benefit over predicted neurological function [2]. Thus, it is clear that further improvements in the prenatal treatment of MMC fetuses are needed.…”
Section: Rationale For Prenatal Surgical Closure Of Myelomeningocelementioning
confidence: 99%
See 1 more Smart Citation
“…The MOMS trial demonstrated conclusively that fetal surgery improves the 12- and 30-month outcomes of MMC patients, with a reduction in hindbrain herniation and the need for shunting and significant improvement in functional neurological outcomes, including the ability to walk without orthotics, setting a new standard for the treatment of eligible MMC fetuses. However, open fetal surgery for MMC is not a cure, with most patients demonstrating some degree of residual neurological deficit and some fetuses demonstrating no benefit over predicted neurological function [2]. Thus, it is clear that further improvements in the prenatal treatment of MMC fetuses are needed.…”
Section: Rationale For Prenatal Surgical Closure Of Myelomeningocelementioning
confidence: 99%
“…The application of an invasive procedure with significant potential risk to the mother was felt to be justified due to the devastating neurological consequences of MMC, including lower extremity paralysis, neurogenic bladder and hindbrain herniation [1,2]. The rationale for fetal treatment is based on the ‘two-hit' hypothesis, where the first ‘hit' is the primary failure of neurulation, and the second ‘hit' is the injury to exposed neural elements caused by exposure to amniotic fluid and mechanical trauma within the amniotic space [3].…”
Section: Rationale For Prenatal Surgical Closure Of Myelomeningocelementioning
confidence: 99%
“…Neurological benefit was difficult to demonstrate. If the technical difficulties with prematurity and graft placement can be overcome, these strategies could eventually prove useful [17]. …”
Section: Special Considerationsmentioning
confidence: 99%
“…These defects occur in 1 of 3,000 live births and are often associated with complex medical symptoms such as mental retardation, orthopedic disabilities and paralysis [1]. Treatment includes surgical repair either at birth or midgestationally and involves closure of the neural tube with maximal preservation of neuronal and surrounding tissue [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…These defects occur in 1 of 3,000 live births and are often associated with complex medical symptoms such as mental retardation, orthopedic disabilities and paralysis [1]. Treatment includes surgical repair either at birth or midgestationally and involves closure of the neural tube with maximal preservation of neuronal and surrounding tissue [1,2]. Despite aggressive treatment, patients with the diagnosis of myelomeningoceles carry a 5-year mortality rate of just under 14%, while those who survive often progress to have severer spinal deformities, such as kyphosis and scoliosis [1].…”
Section: Introductionmentioning
confidence: 99%